Identifying adolescents in the early stage of psychosis: A screening checklist for referrers. Issue 6 (19th November 2021) - Pelizza, Lorenzo; Chiri, Luigi R.; Azzali, Silvia; Garlassi, Sara; Scazza, Ilaria; Paterlini, Federica; Poletti, Michele; Pupo, Simona; Raballo, Andrea
Abstract: Objective: The early identification of adolescents at the onset of psychosis is crucial to provide effective interventions. The aim of this study is to examine the validity of the "early detection Primary Care Checklist" (PCC) in an Italian adolescent population. The PCC is a 20‐item tool designed to assist primary care practitioners in identifying young people with early psychosis. Methods: The checklist was completed by the referring practitioners of 129 adolescents. The validity of this instrument was established by comparing screen results with the "Comprehensive Assessment of At‐Risk Mental States." Results: The simple checklist had excellent 98% sensitivity, but low specificity (58%). Using only a PCC total score of ≥20 as cutoff, there was a substantial improvement in specificity (87%). Conclusion: The Italian version of the PCC performed well to identify adolescents in the early stage of psychosis and may be used in primary care settings.